Vladimir Karlov and the Research Center of Neurology: 70 years together - M. A. Piradov; S. A. Klyushnikov; S. N. Illarioshkin (Эпилепсия и пароксизмальные состояния, 2021)
Multiple aspects covering multiannual close cooperation between Dr. V.A. Karlov and prominent scientists from the Research Center of Neurology have been illuminated in the report. It was shown how an extended study was performed at the joint between two medical disciplines and what importance for the staff had Professor Karlov pedagogical activity.